Pengembangan Kreativitas melalui Pemanfaatan Barang Bekas menjadi Media Edukasi untuk Anak Usia Dini - Setiawan, Anissa Ariyanti; Cuarni, Cuarni; Ardianti, Dini; Kurniati, Iim; Maryana, Maya; Suryani, Nani; Veronika, Vara (MASALIQ, 2023)
The problem that occurred in this study was the lack of creativity of children in using used goods during learning. The purpose of this research is to improve and develop children's creativity so that children are stimulated to express their ideas that make used goods useful items to use. The research method used in this research is descriptive analysis method with a qualitative approach. The population used is 15 children with a sample of 3 participants. The research instrument uses observation guidelines, interview guidelines, and documentation guidelines. Data collection techniques using observation techniques, interviews, and documentation. Data analysis uses data triangulation by reducing data, presenting data, and making conclusions. The result of this study is the increase in children's creativity when processing used goods into works or items that can be useful for use. The conclusion is a way to increase creativity by stimulating children using demonstration methods by the teacher by giving examples first. With this stimulus, there is an increase in children when they come up with new ideas by creating works from used goods into useful items.